Lament for a son - Wolterstorff, Nicholas (Grand Rapids, Mich. : Eerdmans, 1987)
A loving father explores with honesty and intensity all facets of his grief at the death of his 25-year-old son.
Includes bibliographical references.
Keywords: Wolterstorff, Nicholas -- Family; Wolterstorff, Nicholas; Children -- Death -- Psychological aspects; Bereavement -- Psychological aspects; Fathers and sons; Fathers -- United States -- Biography; Bereavement -- Psychological aspects; Children -- Death -- Psychological aspects; Families; Fathers; Fathers and sons; United States; Mochsin, Mochammed -- Sohn; Trauer, ...; Autobiographies; Biography; Autobiographies